Management of severe sepsis in patients admitted to Asian intensive care units: prospective cohort study. (13th June 2011) - Phua, Jason; Koh, Younsuck; Du, Bin; Tang, Yao-Qing; Divatia, Jigeeshu V; Tan, Cheng Cheng; Gomersall, Charles D; Faruq, Mohammad Omar; Shrestha, Babu Raja; Gia Binh, Nguyen; Arabi, Yaseen M; Salahuddin, Nawal; et al.
Abstract : Objectives To assess the compliance of Asian intensive care units and hospitals to the Surviving Sepsis Campaign's resuscitation and management bundles. Secondary objectives were to evaluate the impact of compliance on mortality and the organisational characteristics of hospitals that were associated with higher compliance. Design Prospective cohort study. Setting 150 intensive care units in 16 Asian countries. Participants 1285 adult patients with severe sepsis admitted to these intensive care units in July 2009. The organisational characteristics of participating centres, the patients' baseline characteristics, the achievement of targets within the resuscitation and management bundles, and outcome data were recorded. Main outcome measure Compliance with the Surviving Sepsis Campaign's resuscitation (six hours) and management (24 hours) bundles. Results Hospital mortality was 44.5% (572/1285). Compliance rates for the resuscitation and management bundles were 7.6% (98/1285) and 3.5% (45/1285), respectively. On logistic regression analysis, compliance with the following bundle targets independently predicted decreased mortality: blood cultures (achieved in 803/1285; 62.5%, 95% confidence interval 59.8% to 65.1%), broad spectrum antibiotics (achieved in 821/1285; 63.9%, 61.3% to 66.5%), and central venous pressure (achieved in 345/870; 39.7%, 36.4% to 42.9%). High income countries, university hospitals, intensive care units with an accredited fellowship programme, and surgical intensive care units were more likely to be compliant with the resuscitation bundle. Conclusions While mortality from severe sepsis is high, compliance with resuscitation and management bundles is generally poor in much of Asia. As the centres included in this study might not be fully representative, achievement rates reported might overestimate the true degree of compliance with recommended care and should be interpreted with caution. Achievement of targets for blood cultures, antibiotics, and central venous pressure was independently associated with improved survival.